A New Fluorescence-Based Reporter Gene Vector as a Tool for Analyzing and Fishing Cells with Activated Wnt Signaling Pathway. (28th August 2013) - Apfel, Johanna; Reischmann, Patricia; Müller, Oliver
Abstract : The dysregulated Wnt pathway is a major cause for the activation of cell proliferation and reduced differentiation in tumor cells. Therefore the Wnt signaling pathway is the on-top target in searching for new anticancer drugs or therapeutic strategies. Although the key players of the pathway are known, no specific anti-Wnt drug entered a clinical trial by now. Several screening approaches for potential compounds have been performed with a reporter gene assay using multiple T-cell factor/lymphoid enhancer factor (TCF/LEF) binding motifs as promoters which control luciferase or β -galactosidase as reporter genes. In our work, we designed a reporter gene construct which anchors the enhanced green fluorescent protein (eGFP) to the plasma membrane. HEK 293T cells, which were stably transfected with this construct, express eGFP on the outer membrane after activation with either LiCl or WNT3A protein. Thus, cells with activated Wnt pathway could be identified and fished out of a heterogeneous cell pool by the use of magnetic-labeled anti-GFP antibodies. In summary, we present a new tool to easily detect, quantify, and sort cells with activated Wnt signaling pathway in a simple, fast, and cost-effective way.